Health of the Nation Outcome Scales in a psychiatric inpatient setting: Assessing clinical change. Issue 2 (2nd February 2015) - Egger, Stephan T.; Weniger, Godehard; Prinz, Susanne; Vetter, Stefan; Müller, Mario
Abstract: Rationale, aims and objectives: The aim of this study was to examine the validity of the Health of the Nation Outcome Scales (HoNOS) in terms of change in relation to sex, clinical characteristics and level of clinical change as assessed using other measures. Methods: The sample consisted of N  = 690 admissions from one Swiss psychiatric hospital who were assessed at admission and discharge using the HoNOS and the clinical global impression (CGI) scale. Repeated measures analyses of variance were conducted to compare changes in HoNOS scores over time stratified by sex, diagnostic category and CGI level of change, controlled for age and previous hospitalizations. Two‐way interactions between time and these factors were calculated and post hoc t ‐tests were conducted to compare changes in HoNOS scores between admission and discharge at factor levels. Results: HoNOS scores significantly decreased from admission to discharge in bivariate analyses although no main effect of time was found in multivariate models. Sex was found to moderate change in HoNOS behavioural subscale scores; primary diagnosis at admission moderated change in HoNOS total scores, the behavioural subscale and the social subscale; and CGI level of change moderated the change in all HoNOS scales. Conclusions: Our findings confirmed the sensitivity to change of the HoNOS in psychiatric settings from admission to discharge. Furthermore, we found that this change reflected similar changes in the CGI, a well‐established measure for the evaluation of clinical outcomes, which, in turn supports the validity of the HoNOS.